(3GdeLGdS GdSYjOIs - (3eMeO QVG Hf bGSe Hf eMeO GdZQGhj, J (B1385(3g` (B1965(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdYXje GdTGf Gdbhj GdSdWGf (B... (3GdeLdS GdChd, aj Pe GdZjHI hGdfejeI, HSe Gddg GdQMef GdQMje dG CTO HdGA hdG CYXe YfGA Ydi GdEfSGf ef GdZjHI CP gj CHZV dYdGe GdZjhH eeG YOGgGs
(3BNQgG (B:s
(3BNQgG(B: (3hhaO Ydi GdQVG QLd NQGSGfj aCYWGg Ydjg GdSdGe LejY eG jMJGL Edjg ef Tb GdHGH abjd dg aj Pdc abGd Ydjg GdSdGe, aYdJ Pdc eNGaI Cf CQi Pd GdSDGds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 128s
(3GdPQjYI, L (B19: 247s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs